Pembuatan Bioetanol Dari Limbah Kulit Durian Menggunakan Proses Fermentasi - Jeanne Salwa Saphira Reza; Muhammad Yerizam; Linda Ekawati (Universitas Batanghari Jambi, 2025)
The utilization of durian peels, which are considered agricultural waste, remains minimal. One alternative to reduce the amount of durian peel waste is to use it as a basic material for producing bioethanol. Durian peels contain a significant amount of cellulose, making them highly potential as a basic material for bioethanol production. One of the key processes in producing bioethanol is fermentation, which is carried out with the help of microorganisms, specifically those from baker’s yeast or Saccharomyces cerevisiae. This experiment was conducted to determine the effect of fermentation duration and yeast mass on the resulting bioethanol content. The independent variables in this study are fermentation time and the mass of yeast used. The fermentation times used are 24, 48, 72, 96, and 120 hours, with yeast mass concentrations of 2%, 4%, and 6% mass/volume. After fermentation, the process continues to the purification or distillation stage to obtain the final bioethanol product. The obtained bioethanol will then be measured for its refractive index and analyzed using Gas Chromatography to determine its bioethanol content (%). The highest bioethanol content observed in this experiment was 29.33%, achieved with a fermentation time of 72 hours and a yeast mass of 6%. The quantitative analysis using GC showed the highest bioethanol content of 29.70%. These results indicate that durian peel waste has significant potential as a basic material for bioethanol production.